1978
DOI: 10.1136/pgmj.54.631.323
|View full text |Cite
|
Sign up to set email alerts
|

The problems of massive small bowel resection and difficulties encountered in management

Abstract: Summary Massive small bowel resection is imperative in the management of several pathological conditions and is accompanied by high operative mortality. In those that survive, serious nutritional disturbances are inevitable. Intestinal adaptation is said to occur but cannot be relied upon. Long-term parenteral nutrition is problematical and often unsuccessful. Many surgical procedures have been adopted in an effort to improve prognosis and have been found wanting. Controlled experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In some cases, well-documented increases in intestinal absorption have been produced whilst in others no clear advantage was gained [7]. In clinical practice however, the behaviour of the reversed segment has been unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, well-documented increases in intestinal absorption have been produced whilst in others no clear advantage was gained [7]. In clinical practice however, the behaviour of the reversed segment has been unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice however, the behaviour of the reversed segment has been unpredictable. In some cases, well-documented increases in intestinal absorption have been produced whilst in others no clear advantage was gained [7]. An improved understanding of the physiological response of the intestine to the retrograde flow of luminal contents might allow segmental reversal or similar procedures to be used with greater success in treating the short bowel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, there do appear to be in the literature a small number of patients in whom the procedure has been performed successfully. In a review of 29 published cases, Barros D'Sa [36] found satisfactory to excellent results in 23 patients. In practical terms, the types of patient on whom one can use reversed loops are quite limi~ed.…”
Section: The Place Of Further Surgerymentioning
confidence: 97%